Tumor cell invasion in blood vessels assessed by immunohistochemistry is related to decreased survival in patients with bladder cancer treated with radical cystectomy - Birgitte Carlsen; Tor Audun Klingen; Bettina Kulle Andreassen; Erik Skaaheim Haug (BMC, 2021)
Abstract Background Lymphovascular invasion (VI) is an established prognostic marker for many cancers including bladder cancer. There is a paucity of data regarding whether the prognostic significance of lymphatic invasion (LVI) differs from blood vessel invasion (BVI). The aim was to examine LVI and BVI separately using immunohistochemistry (IHC), and investigate their associations with clinicopathological characteristics and prognosis. A secondary aim was to compare the use of IHC with assessing VI on standard HAS (hematoxylin-azophloxine-saffron) sections without IHC. Methods A retrospective, population -based series of 292 invasive bladder cancers treated with radical cystectomy (RC) with curative intent at Vestfold Hospital Trust, Norway were reviewed. Traditional histopathological markers and VI based on HAS sections were recorded. Dual staining using D2-40/CD31 antibodies was performed on one selected tumor block for each case. Results The frequency of LVI and BVI was 32 and 28%, respectively. BVI was associated with features such as higher pathological stages, positive regional lymph nodes, bladder neck involvement and metastatic disease whereas LVI showed weaker or no associations. Both BVI and LVI independently predicted regional lymph node metastases, LVI being the slightly stronger factor. BVI, not LVI predicted higher pathological stages. BVI showed reduced recurrence free (RFS) and disease specific (DSS) survival in uni-and multivariable analyses, whereas LVI did not. On HAS sections, VI was found in 31% of the cases. By IHC, 51% were positive, corresponding to a 64% increased sensitivity in detecting VI. VI assessed without IHC was significantly associated with RFS and DSS in univariable but not multivariable analysis. Conclusions Our findings indicate that BVI is strongly associated with more aggressive tumor features. BVI was an independent prognostic factor in contrast to LVI. Furthermore, IHC increases VI sensitivity compared to HAS.